(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate factors associated with the outcomes of percutaneous coronary intervention (PCI) after 6 months in patients aged ≥75 years with ST-elevation myocardial infarction (STEMI). Subjects and Methods: A prospective, interventional, cross-sectional study was conducted on 104 patients aged ≥75 years, diagnosed with acute STEMI and indicated for PCI at Vietnam National Heart Institute – Bach Mai Hospital, Hanoi Heart Hospital, and Huu Nghi Hospital during the period 2018–2023. Results: The incidence of major adverse cardiovascular events (MACE) at 6 months post-PCI was 18.3%. The risk factors significantly associated with MACE were: age ≥85 years (OR = 5.39; p = 0.020), diabetes mellitus (OR = 2.95; p = 0.037), Killip class III+IV (OR = 4.44; p = 0.011), TIMI risk score >6 (OR = 3.84; p = 0.019), CK-MB >39 (OR=3.35, p = 0.019), TroponinT T>4084.2 ng/L (OR = 8.02, p<0.001), ST-segment elevation ≥4.0 mm (OR = 4.03; p = 0.009), triple-vessel disease (OR = 3.39; p = 0.016), and left main coronary artery (LMCA) lesion (OR = 4.27; p = 0.046). Conclusion: The factors associated with adverse outcomes following PCI in patients aged ≥75 years with STEMI within 6 months were advanced age, diabetes, high Killip class, elevated TIMI score (>6), lower CK-MB concentration, Troponin T concentration, ST elevation ≥4.0 mm, triple-vessel coronary artery disease, and LMCA involvement.